ANALISIS NILAI-NILAI AGAMA DAN MORAL DALAM TAYANGAN UPIN IPIN SEASON 5 IKHLAS DARI HATI PADA ANAK KELOMPOK A DI RA MAMBAIL FALAH - Rosida; Warih Windasari, Indriana (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
The aim of this study is to explore and elucidate the religious and ethical principles conveyed in the Upin Ipin season 5 episode titled "Ikhlas dari Hati," and to assess its influence on children's spiritual and moral growth. This research employs a descriptive qualitative approach, utilizing both primary and secondary data sources. Data gathering methods encompass observation, interviews, and documentation, while data analysis involves content analysis, data scrutiny, and reconstruction. The findings reveal that "Ikhlas dari Hati" episode of Upin Ipin portrays various religious and moral values, including integrity, acceptance, kindness, charity, assistance, collaboration, discipline, and reverence. Interview outcomes further demonstrate that Upin Ipin episodes can positively impact children's character development, fostering behaviors such as treating others with kindness and respect, offering assistance, and instilling other constructive values. Furthermore, this influence extends beyond mere knowledge acquisition, also influencing children's language patterns in their daily interactions. This occurs as children tend to readily emulate what they observe and hear, swiftly integrating these behaviors into their everyday lives. Keywords : Religious and Moral Values, Early Childhood, Upin Ipin Films